Culinary exploitation of nopal cactus pear in arid region - Saroj, P L; Singh, Dhurendra; Kumar, Kamlesh (Indian Horticulture, 2019)
In India, cacti were largely known as ornamental plants and find placeeither as component of rock garden or planted in pots in kitchen garden.Sometimes, thorny cactus plants are also planted along the field boundariesas live fences. It can also be seen growing in wild form in forest andwastelands. However, cactus as edible plant (fruits/ leaf pads) was largelyignored till recently by the scientific community but with increasingawareness about diversified usages and health promoting benefits; someorganizations started collection and evaluation of cactus pear in India.Moreover, it has not gained momentum due to its inherent constraints likethorny nature, low fruit yield and poor shelf life of fruits. At Central Institutefor Arid Horticulture, Bikaner, we have selected a cactus clone of nopalesgroup having thorn less cladodes (leaf pads) at tender stage and can beutilized for delicious culinary preparations like vegetable, salad and pickles;while fruits for preparation of attractive pink colour syrup as well asextraction of natural colorant used in food and dairy industries. This clonecan be cultivated in tropical and semi-arid regions as rainfed and in hotarid region under limited irrigation with caution that it should be protectedfrom animals and wild life as its cladodes are very tasty.